From production to market; enhancing food security through efficient mushroom distribution: A study of energy and economic evaluations - Mina Shafei Galeh; Mahmoud Ghasemi-Nejad-Raeini; Morteza Taki (Results in Engineering)
Considering the significance of food security as a global challenge, access to sufficient and high-quality food resources is essential. Edible mushrooms, due to their rich protein and caloric content, play a crucial role in meeting nutritional needs. This study aims to evaluate the qualitative, energy-economic, and technical efficiency aspects of two mushroom distribution methods—packaged and bulk—in the production chain. Data were collected from 35 button mushroom production units in Khuzestan province through questionnaires and face-to-face interviews. The results showed that the total energy consumption for packaged and bulk distribution was 66,664 MJm−2 and 63,572 MJm−2, respectively, while the total energy output was 13.36 MJm−2 and 30.96 MJm−2. Compost was identified as the primary energy-consuming input, accounting for 72.08 % in the packaged method and 76.12 % in the bulk method. Diesel fuel ranked second in energy consumption. The energy ratio was calculated as 0.05 for packaged distribution and 0.06 for bulk distribution. Additionally, the total revenue for packaged and bulk methods was 5608.69$ and 2279.26$ per 100 m−2, while production costs were 1747.25$ and 1356.70$ per 100 m−2, respectively. The benefit-cost ratio was 3.21 for packaged distribution and 1.68 for bulk distribution. The mean technical efficiency, pure technical efficiency, and scale efficiency were estimated at 0.950, 0.910, and 0.958, respectively. Data analysis revealed that mushroom quality (color) was significantly affected on the fourth, sixth, and seventh days, while weight loss was significant on all days except the seventh. Bulk distribution exhibited the most significant color change on the fifth and seventh days and the highest weight reduction on the first and fifth days.